Sharks as apex predators in the Late Cretaceous Western Interior Seaway empirically revealed by zinc isotope analyses - Jeremy McCormack; Harry Maisch IV; Martin A. Becker; Michael L. Griffiths; Jade Knighton; Robert A. Eagle; Kevin Stevens; Wolfgang Müller; Kenshu Shimada (Gondwana Research, 2026)

A sub-chondritic nickel stable isotope composition of Mars - Ke Zhu; Martijn Klaver; Wei-Biao Hsu; Harry Becker; Lu Chen; Qi Chen (Geochimica et Cosmochimica Acta, 2026)

Isotopic fractionation of copper during silicate melt evaporation: effects of sulfur, fO2, and temperature - Guillaume Florin; Paul Pangritz; Christian J. Renggli; Philipp Gleißner; Jasper Berndt; Arno Rohrbach; Harry Becker; Stephan Klemme (Geochimica et Cosmochimica Acta, 2025)

Copper isotopes in mare basalts reveal metal-silicate equilibration in the lunar magma ocean - Guillaume Florin; Philipp Gleißner; Harry Becker (Geochimica et Cosmochimica Acta, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Moderately volatile elements in chondrites record chondrule formation, two-component mixing and redistribution on parent bodies - Ninja Braukmüller; Claudia Funk; Wafa Abouchami; Harvey Pickard; Mark Rehkämper; Alessandro Bragagni; Stephen J.G. Galer; Carsten Münker; Harry Becker; Frank Wombacher (Geochimica et Cosmochimica Acta, 2025)

Young KREEP-like mare volcanism from Oceanus Procellarum - Zaicong Wang; Keqing Zong; Yiheng Li; Jiawei Li; Qi He; Zongqi Zou; Harry Becker; Frédéric Moynier; James M.D. Day; Wen Zhang; Yuqi Qian; Long Xiao; et al. (Geochimica et Cosmochimica Acta, 2024)

Sulfide compositions of young Chang’e-5 basalts and implications for sulfur isotopes in lunar basalt sources - Zaicong Wang; Yiheng Li; Wen Zhang; Qi He; Fabin Pan; Zhaochu Hu; Keqing Zong; Yantong Feng; Harry Becker; James M.D. Day; Wenlei Song; Hejiu Hui; et al. (Geochimica et Cosmochimica Acta, 2024)

Enigmatic carbonate isotope values in shark teeth: Evidence for environmental and dietary controls - Molly E. Karnes; Rachel L. Chan; Jonathon P. Kuntz; Michael L. Griffiths; Kenshu Shimada; Martin A. Becker; Harry M. Maisch; Robert A. Eagle; Joan Brenner-Coltrain; Shawn Miller; Sora L. Kim (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Community recommendations for geochemical data, services and analytical capabilities in the 21st century - Marthe Klöcking; Lesley Wyborn; Kerstin A. Lehnert; Bryant Ware; Alexander M. Prent; Lucia Profeta; Fabian Kohlmann; Wayne Noble; Ian Bruno; Sarah Lambart; Halimulati Ananuer; Nicholas D. Barber; et al. (Geochimica et Cosmochimica Acta, 2023)

Nano- and micro-structures in lunar zircon from Apollo 15 and 16 impactites: implications for age interpretations - Monika A. Kusiak; Elizaveta Kovaleva; Dennis Vanderliek; Harry Becker; Franziska Wilke; Anja Schreiber; Richard Wirth (Contributions to Mineralogy and Petrology, 2022)
Meteorite impact processes are ubiquitous on the surfaces of rocky and icy bodies in the Solar System, including the Moon. One of the most common accessory minerals, zircon, when shocked, produces specific micro-structures that may become indicative of the age and shock conditions of these impact processes. To better understand the shock mechanisms in zircon from Apollo 15 and 16 impact breccias, we applied transmission electron microscopy (TEM) and studied nano-structures in eight lunar zircons displaying four different morphologies from breccias 15455, 67915, and 67955. Our observations revealed a range of shock-related features in zircon: (1) planar and non-planar fractures, (2) “columnar” zircon rims around baddeleyite cores, (3) granular textured zircon, in most cases with sub-µm-size inclusions of monoclinic ZrO 2 (baddeleyite) and cubic ZrO 2 (zirconia), (4) silica-rich glass and metal inclusions of FeS and FeNi present at triple junctions in granular zircon and in baddeleyite, (5) inclusions of rutile in shocked baddeleyite, (6) amorphous domains, (7) recrystallized domains. In many grain aggregates, shock-related micro-structures overprint each other, indicating either different stages of a single impact process or multiple impact events. During shock, some zircons were transformed to diaplectic glass (6), and others (7) were completely decomposed into SiO 2 and Zr-oxide, evident from the observed round shapes of cubic zirconia and silica-rich glass filling triple junctions of zircon granules. Despite the highly variable effect on textures and Zr phases, shock-related features show no correlation with relatively homogeneous U–Pb or 207 Pb/ 206 Pb ages of zircons. Either the shock events occurred very soon after the solidification or recrystallization of the different Zr phases, or the shock events were too brief to result in noticeable Pb loss during shock metamorphism.

Chondrichthyans from the Lower Clayton Limestone Unit of the Midway Group (Paleocene) near Malvern, Arkansas, USA, with comments on the K/Pg boundary - Harry M. Maisch; Martin A. Becker; Michael L. Griffiths (PalZ, 2020)

Implications of low fiber levels in finishing lambs on performance, health, rumen, and carcass parameters - Sarita Bonagurio Gallo; Thais Brochado; Roberta Ariboni Brandi; Ives Cláudio da Silva Bueno; Daniele Passareli; Daniela Becker Birgel; Eduardo Harry Birgel Junior (Tropical Animal Health and Production, 2019)

The TNFα receptor TNFRSF1A and genes encoding the amiloride-sensitive sodium channel ENaC as modulators in cystic fibrosis - Frauke Stanke; Tim Becker; Harry Cuppens; Vinod Kumar; Jean-Jacques Cassiman; Silke Jansen; Dragica Radojkovic; Benny Siebert; Jennifer Yarden; David W. Ussery; Thomas F. Wienker; Burkhard Tümmler (Human Genetics, 2006)

Petrological constraints on the cooling history of high-temperature garnet peridotite massifs in lower Austria - Harry Becker (Contributions to Mineralogy and Petrology, 1997)

Characterization of the tobacco glycoprotein surface binding property of heart and skeletal muscle cells - Charles A. Santos-Buch; Harry R. Hall; Fausto Farfan; Irene Orlow; Adolfo Firpo; Betsy F. von Kreuter; Carl G. Becker (Archives of Toxicology, 1995)